Spatial Disparities of Sustainable Development Indicators (Unemployment and Poverty) in Iraq for the Year 2021 - A’naad Ghayadh AL-Ojaily, Prof. Dr. Adnan (Basra studies journal, 2024)
The issues of unemployment and poverty are attention-grabbing and worrisome, as they have become significant threats to public life by destabilizing social and security stability, creating a fertile environment for the proliferation of crime and criminals. Moreover, the lack of services such as education and healthcare lead to the spread of underdeveloped areas that harbor various problems. Unemployment is one of the major reasons contributing to the spread of poverty, placing a large number of families under the pressure of severe economic hardships, especially low-income families. The research discusses the most important types of unemployment and poverty, investigates the underlying reasons for their formation, and examines their disparities across the provinces of the country.